Simulasi Perubahan Hidrologi Permukaan Kawasan Karst Sebagai Dampak Ekploitasi Bahan Baku Semen Menggunakan Metode Tangible Landscape - Cendi Tito Rahman; Fatwa Ramdani; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Indonesia is the largest country that has karst area in southeast asia, karst area is rocky arid land, besides that, this area also in exploitation for the needs of cement-making raw materials, but from these mines there will be problems such as the disappearance or changing of hydrology and landscape in karst areas. the need for a preliminary analysis of the impact of mining is very important in the early stages, the technology used to solve the problem in the karst area is still minimal, this is the background of researchers to know the hydrological changes in the karst area impact of exploitation of cement raw materials by simulating the exploitation using the tangible landscape method, this research will visualize in real-time changes in elevation, contour and hydrological results of the exploitation, from the visualization results will be used to take tactical steps for related parties. The results obtained in this study is, mining activities in the area can affect the surface hydrology and environmental topography, then the results of different analytic testing obtained suitability model of 76.5%, Tangible Landscape influenced by the cell value contained in the data and the resulting scale, 10 cm x 10 cm in size produces 3,306 cells while in size 28 cm x 28 cm produces 13.328 cell, then for User Experience testing can be concluded that, this method has a positive experience level to the user see the results of UEQ. Overall Tangible Landscape can be used to visualize environmental changes that occur and can model the environment.